Resiliensi Perempuan Pasca Mengalami Perselingkuhan dan Kekerasan dalam Rumah Tangga di Kabupaten Sukabumi - Shafa Azzahra (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Infidelity and domestic violence (DV) are social problems that significantly impact women’s psychological, social, and economic conditions. This study aims to describe and analyze the resilience of women after experiencing infidelity and domestic violence in Sukabumi Regency. The research employed a qualitative method with a phenomenological approach to explore the lived experiences of women who survived marital conflict. Data were collected through in-depth interviews with five women who had experienced infidelity and domestic violence. The findings reveal that women’s resilience is not formed instantly but develops through a gradual process beginning with a phase of emotional breakdown, followed by adaptation, and eventually leading to the reconstruction of a more independent life. Resilience is manifested through mental and spiritual strengthening, economic independence, and support from family and the social environment. The study also shows that resilience is not merely an individual capacity but is shaped by social structures, cultural norms, and contextual factors surrounding the women’s lives.
Finalisasi Repo 23 Juni 2026_Yudi
Keywords: Resilience; Women; Infidelity; Domestic Violence